Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s13019-017-0679-0
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term results of mitral valve repair using flexible bands versus complete rings in patients with degenerative mitral valve disease: a prospective, randomized study

Abstract: BackgroundWe aimed to compare the outcomes of mitral valve repair with flexible band (FB) versus complete semirigid ring (SR) in degenerative mitral valve disease patients.MethodsFrom September 2011 to 2014, 171 patients were randomized and underwent successful mitral valve repair using a SR (n = 85) or FB (n = 86). There were no significant between-group differences at baseline.ResultsThere were no early mortalities. The mean follow up was 24.7 months. The 2-year survival was 96.0 ± 2.3% (95% confidence inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…In the current study an average of 3.6 chordae per patient have been implanted, within a mean cross clamp time of 53 minutes in isolated MV-repair and 69 minutes in commitment procedures. These findings are comparable to reports from other investigators, where a mean of 4 to 8 PTFE-chordae per patient were required for a repair within a mean cross clamp time of ∼84-101 minutes based on the type of procedure (15,16).…”
Section: Discussionsupporting
confidence: 88%
“…In the current study an average of 3.6 chordae per patient have been implanted, within a mean cross clamp time of 53 minutes in isolated MV-repair and 69 minutes in commitment procedures. These findings are comparable to reports from other investigators, where a mean of 4 to 8 PTFE-chordae per patient were required for a repair within a mean cross clamp time of ∼84-101 minutes based on the type of procedure (15,16).…”
Section: Discussionsupporting
confidence: 88%
“…On the contrary, Spiegelstein et al in a retrospective study showed that in degenerative MR, PR was associated with lower rates of recurrent MR than fl exible rings. 28 A comparison of pericardial and CR annuloplasty also reported similar clinical and echocardiographic outcomes. 5 David et al as well as Okada et al showed signifi cantly better LV function with fl exible rings than with rigid rings 9,15 whilst Bogachev et al reported that LV changes were more signifi cant in the fl exible bands than in rigid rings.…”
Section: Discussionmentioning
confidence: 72%
“…Among the mitral studies, 6 used semi-rigid [ 6 , 7 , 9 , 13 , 20 , 27 ], 5 used rigid [ 10 , 13 , 14 , 18 , 24 ], 5 used flexible [ 8 , 11 , 12 , 19 , 27 ] and 2 used biological rings [ 17 , 25 ]. The incidence of dehiscence among ring types was the following: 0.04% flexible; 1.55% semi-rigid; 2.96% rigid and 3.07% in biological (number of patients, respectively: 784; 3750; 608; 163).…”
Section: Resultsmentioning
confidence: 99%